Transport Costs in International Trade Theory: A Comparison with the Analysis of Nontraded Goods - Cassing, James H. (Quarterly Journal of Economics, 1978)
I. Assumptions and notation, 536. — II. The model, 537. — III. The equations of change, 540. — IV. Autonomous price changes, 541. — V. Factor accumulation, 543. — VI. Conclusions, 548.